On the Relationship Between Attention Processing and P300-Based Brain Computer Interface Control in Amyotrophic Lateral Sclerosis - Riccio, Angela; Schettini, Francesca; Simione, Luca; Pizzimenti, Alessia; Inghilleri, Maurizio; Olivetti-Belardinelli, Marta; Mattia, Donatella; Cincotti, Febo (Frontiers in Human Neuroscience, 2018)
Our objective was to investigate the capacity to control a P3–based BCI device for communication and its related (temporal) attention processing in a sample of Amyotrophic Lateral Sclerosis (ALS) patients with respect to healthy subjects. The ultimate goal was to corroborate the role of cognitive mechanisms in ERP-based BCI control in ALS patients. Furthermore, the possible differences in such attentional mechanisms between the two groups were investigated in order to unveil possible alterations associated with the ALS condition. Thirteen ALS patients and 13 healthy volunteers matched for age and years of education underwent a P3-speller BCI task and a rapid serial visual presentation (RSVP) task. The RSVP task was performed by participants in order to screen their temporal pattern of attentional resource allocation, namely: i) the temporal attentional filtering capacity (scored as T1%) and ii) the capability to adequately update the attentive filter in the temporal dynamics of the attentional selection (scored as T2%). For the P3-speller BCI task, the online accuracy and Information Transfer Rate (ITR) were obtained. Centroid Latency and Mean Amplitude of N200 and P300 were also obtained. No significant differences emerged between ALS patients and Control with regards to online accuracy (p=.13). Differently, the performance in controlling the P3-speller expressed as ITR values (calculated offline) were compromised in ALS patients (p<.05), with a delay in the latency of P3 when processing BCI stimuli as compared with Control group (p<.01). Furthermore, the temporal aspect of attentional filtering which was related to BCI control (r=0.51; p<.05) and to the P3 wave amplitude (r=0.63; p<.05) was also altered in ALS patients (p=.01). These findings ground the knowledge required to develop sensible classes of BCI specifically designed by taking into account the influence of the cognitive characteristics of the possible candidates in need of a BCI system for communication.